Combined laparoscopic pyelolithotomy and endoscopic pyelolithotripsy for staghorn calculi: long-term follow-up results from a case series. (February 2016) - Pastore, Antonio Luigi; Palleschi, Giovanni; Silvestri, Luigi; Leto, Antonino; Ripoli, Andrea; Fuschi, Andrea; Al Salhi, Yazan; Autieri, Domenico; Petrozza, Vincenzo; Carbone, Antonio
Purpose: Staghorn renal stones are a challenging field in urology. Due to their high recurrence rates, particularly those associated with an infective process, a complete removal is the ultimate goal in their management. We report our experience with a combined approach of laparoscopic pyelolithotomy and endoscopic pyelolithotripsy, the stone clearance rate, and long-term, follow-up outcomes. Methods: From June 2012 to October 2014, nine adult patients with large staghorn renal calculi (mean size, 7.2 cm; range, 6.2–9.0 cm) underwent a combined laparoscopic and endoscopic approach. The technique comprised laparoscopic pyelolithotomy and holmium-YAG laser stone fragmentation with the use of a flexible cystoscope introduced through a 12 mm trocar. Results: The average operative time was 140 min (range, 90–190 min). The mean estimated hemoglobin loss was 0.6 mmol/l (range 0.5–0.7 mmol/l). None of the patients required an open- surgery conversion. The mean hospital stay was 4 days (range, 2–6 days). A computed tomography urogram control at 6 months of follow up did not show any stone recurrence. Conclusions: Laparoscopic pyelolithotomy combined with endoscopic pyelolithotripsy could be a therapeutic option in cases where mini-invasive procedures, that is, extracorporeal shock wave lithotripsy, ureteroscopic lithotripsy, and percutaneous nephrolithotomy (PCNL) have failed. This technique has a high stone-clearance rate (75–100%) comparable with open surgery and PCNL. However, it could be technically demanding and should be performed by skilled laparoscopy surgeons.